Dental injury during seizures associated with juvenile myoclonic epilepsy. Issue 1 (16th December 2008) - Thomas, R H; Higgins, S; Fuller, G N
Abstract : Background: Patients can sustain injuries during seizures and the pattern and type of injury (eg, tongue biting) can be a useful silent witness in the diagnosis of seizures. In addition, the seizure type potentially influences the type of injury. Methods: Patients with dental injury were identified from the Gloucestershire Epilepsy Database (n = 1673). These patients' notes were reviewed and the following data collected: demographic data; seizure types and age of onset; injury; EEG; and MRI. Results: 14 people had dental injuries: 10 incisors (seven had >1 incisor) and five other teeth. Eight had juvenile myoclonic epilepsy (JME), two other primary generalised epilepsy and four focal onset epilepsy. Compared with the rest of the database population (JME; n = 81) there was a highly significant association of dental injury with JME (p<0.0001). Conclusions: Incisor injury is rare but appears to be associated with JME in patients with epilepsy, presumably reflecting the pattern of seizure onset. This pattern of injury should prompt consideration of this diagnosis. It is hoped that recognition of this can both facilitate earlier diagnosis and help educate patients to protect their teeth.